Impact of Lamaze Breathing on Childbirth- Comparison Between Primigravid and Multigravid Women - Sushmitha R Karkada; Judith A Noronha; Shashikala K Bhat (Medsci Publications, 2024)
Introduction: The most basic function of life, breathing promotes awareness, attentiveness, alertness, and focus in women. The Lamaze technique's goals are to promote, maintain, and protect a healthy pregnancy and a safe delivery. In this study, primigravid and multigravida women were compared with respect to the effects of the Lamaze technique on duration of labor and neonatal outcomes. Methodology: Primigravid and multigravid women who met the eligibility criteria were randomized into intervention and standard care groups in a parallel group randomized controlled study. After 36 weeks of pregnancy, the researcher introduced the women in the experimental groups the Lamaze techniques. The length of labor and neonatal outcomes between the primigravid and multigravid women in the intervention group and the standard care group were used to measure the result. Results: The mean duration of labor was shorter in the intervention groups. The Mann-Whitney U test indicated a statistically significant difference in the duration of labor between women who practiced Lamaze breathing during pregnancy and those who did not (U = 5742, p < 0.05). Conclusion: The present study concludes that Lamaze techniques during the antenatal period shortens labor duration and accelerates labor progress, hence facilitating natural childbirth.